Answer:
D = 120, there are 2 real roots for F(x)
Step-by-step explanatU
using the
formula D = b^2 - 4ac for discriminant
D = 8^2 - 4*(-7)*2
D = 64 + 56 = 120
Answer:
28 inches
Step-by-step explanation:
P = 2 (a + b) = 2 · (6 + 8) = 28
9514 1404 393
Answer:
32
Step-by-step explanation:
The first term is 5 and the common difference is 9-5=4, so the n-th term is ...
an = a1 +d(n -1)
an = 5 +4(n -1) = 4n +1
Then the term number for the term 129 is ...
129 = 4n +1 . . . . . put the given value in the formula
128 = 4n . . . . . . . subtract 1
32 = n . . . . . . . . . .divide by 4
The 32nd term is 129.
Answer:
y = 2*x^2 - 2*x - 24
Step-by-step explanation:
If we have a quadratic function with roots a and b, we can write the equation for that function as:
y = f(x) = A*(x - a)*(x - b)
Where A is the leading coefficient.
In this case, we know that the roots are: 4 and -3
Then the function will be something like:
f(x) = A*(x - 4)*(x - (-3) )
f(x) = A*(x - 4)*(x + 3)
Now we need to determine the value of A.
We also know that the graph of the function passes through the point (3, -12)
This means that:
f(3) = -12
Then:
-12 = A*(3 - 4)*(3 + 3)
-12 = A*(-1)*(6)
-12 = A*(-6)
-12/-6 = A
2 = A
Then the equation is:
y = f(x) = 2*(x - 4)*(x + 3)
Now we need to write this in standard form, so we just need to expand the equation:
y = f(x) = 2*(x^2 + x*3 - x*4 - 4*3)
y = f(x) = 2*(x^2 - x - 12)
y = f(x) = 2*x^2 - 2*x - 24
Then the relation is:
y = 2*x^2 - 2*x - 24